A Comparative Study of Sustainability Disclosure Practices of India and USA. (March 2013) - Tuli, Siya
Sustainable development efforts presented on a piece of paper take the shape of a sustainability report, also labelled as sustainable development report. Sustainability report integrates economic, environmental and social performance of the company into one report. This study compares the sustainable development efforts by companies in developed (USA) and developing (India) nations. The recent sustainability reports from a three-year period that is 2008–2011 of AMEX major market index (USA) and SENSEX companies (India) are studied using content analysis. Independent sample t test and ANOVA have been used to compare the reports of the said countries. The results of the analysis show that companies are now more aware of sustainable development. Out of 20 AMEX major market index companies, 14 companies are providing sustainability information in a separate sustainability report while in case of SENSEX there are 16 companies out of 30 that are producing sustainability reports. In USA greater percentage of companies is disclosing sustainability information, while the quantity of information disclosed as per GRI's G3 guidelines, in sustainability reports is more in the case of Indian companies.